Margin Analysis and Efficiency of the Day Old Duck (DOD) Marketing Channel (Case Study on Adam Gobek Lareh Sago Halaban) - Sischa Febriani Yamesa Away; Defidelwina Defidelwina (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
Through creating and exchanging products and value with others, marketing is a social and management activity that enables individuals and groups to fulfill their needs and desires. This study analyzes DOD's channels, margins, profits, and marketing efficiency in Adam Gobek Lareh Sago Halaban hatchery. This research was conducted from March 2021 to May 2021. The data collection method used was a survey method. This research is a case study on Adam Gobek Lareh Sago Halaban to determine the sample in the marketing channel used snowball sampling. The results showed five marketing channels for DOD in Adam Gobek's hatchery business. The highest marketing margin is in marketing channel IV, amounting to IDR2,000.00/tail. In contrast, the marketing channel with the lowest Margin is marketing channel II of IDR940/tail. The highest marketing profit is marketing channel I of IDR861/director, while the marketing channel with the lowest profit is marketing channel II of IDR292/tail. A very efficient marketing channel is marketing channel I, with a percentage of 1.7%, while inefficient marketing is visible on marketing channel IV, with a percentage of 5.6%.